2013
DOI: 10.1002/stem.1423
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Deficiency of Lin28 Programs Life-Long Aberrations in Growth and Glucose Metabolism

Abstract: LIN28A/B are RNA binding proteins implicated by genetic association studies in human growth and glucose metabolism. Mice with ectopic over-expression of Lin28a have shown related phenotypes. Here we describe the first comprehensive analysis of the physiologic consequences of Lin28a and Lin28b deficiency in knockout (KO) mice. Lin28a/b-deficiency led to dwarfism starting at different ages, and compound gene deletions showed a cumulative dosage effect on organismal growth. Conditional gene deletion at specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
128
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 37 publications
(3 reference statements)
7
128
2
1
Order By: Relevance
“…Moreover, Lin28 has been shown to promote glycolytic metabolism in tissues and cancer cells and thus is a central regulator of cellular bioenergetics ). It appears that Lin28 functions to balance the proliferative and metabolic needs of rapidly growing cells in the early embryo (Shinoda et al 2013b) and that this function becomes reactivated in many adult tumors. In cases of pediatric malignancy, Lin28 appears to prolong the embryonic patterns of tissue growth (as we showed here for Wilms tumor), which is likely the case for germ cell tumors and neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lin28 has been shown to promote glycolytic metabolism in tissues and cancer cells and thus is a central regulator of cellular bioenergetics ). It appears that Lin28 functions to balance the proliferative and metabolic needs of rapidly growing cells in the early embryo (Shinoda et al 2013b) and that this function becomes reactivated in many adult tumors. In cases of pediatric malignancy, Lin28 appears to prolong the embryonic patterns of tissue growth (as we showed here for Wilms tumor), which is likely the case for germ cell tumors and neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Initial investigations have revealed roles for LIN28 in glucose uptake and tolerance, diabetes, sickle cell anemia and cancer (de Vasconcellos et al, 2014;Perez et al, 2013;Shinoda et al, 2013;Shyh-Chang et al, 2013;Zhu et al, 2011), suggesting that the modulation of LIN28 activity might be an attractive therapeutic approach. For example, the expression of LIN28 in cultured, sickle-shaped erythrocytes resulted in a significant decrease in their sickle morphology compared with control erythrocytes (de Vasconcellos et al, 2014).…”
Section: Lin28 In Disease and Therapymentioning
confidence: 99%
“…S1E) prompted us to examine whether they play redundant roles in brain development. It has been reported that Lin28b null mice exhibit no detectable developmental phenotypes (Shinoda et al, 2013). We crossed Lin28a +/− with Lin28b +/− mice to produce compound heterozygotes, which were intercrossed to generate various genotypes including double-homozygous knockout (DKO) offspring.…”
Section: Lin28a and Lin28b Are Both Required For Normal Npc Proliferamentioning
confidence: 99%
“…Lin28b knockout mice were kindly provided by the Dr George Daley laboratory, and have been described elsewhere (Shinoda et al, 2013).…”
Section: Lin28a/b Mutant and Lin28a Transgenic Micementioning
confidence: 99%